Measurement of CD4 and CD8 in Cutaneous Leishmanisis Patientsand their Relation tvith Zn Deficiency - A. Salman and Azad Kamal, Abed; R. Sarhat, Ashoor; S. Aswed Al-Obaidi, Hussein (Tikrit Journal of Pharmaceutical Sciences, 2023)
Cutaneous leishmainasis still is a common skin infection worldwide and because it's type and of clinical course depends on patient's immune system which in turn affected by zinc. To assess the relation of serum zinc, CD4", and CD8" with the disease. A total of 107 patients with CL were studied during period between October/2004-April/2005 in the dermatology department of Al- Haweja general hospital. Patients were divided in to two groups according to immune system development and Zn requirement. Sixty healthy individuals were used as control group, and divided into two groups, first groups 20 individuals' ages ranging from 1-15 years and second groups above 15 years their ages ranging from 16 to 60 years and sub-divided into 20 males and 20 females. After history and examination confimation of diagnosis made by skin smears. Serum zinc level and CD4* and CD8" were done for all patients and control. The mean of serum Zn concentration in patients above 15 years of age was significantly low 7.61 = 0.03 pmol / | for male, and 6.69+ 0.31 for female in comparison to 14.08 = 0.04 pmol/l for male, and 12.02 + 0.02 for female in similar control group. The mean percent of CD4" in patients above 15 years of age was significantly low 36.5 + 0.98% for male, and 36.29 = 0.06 % for female in comparison to 59.95 = 0.16%% for male, and 58.90.14 % for female in similar control group. The mean percent of CDS” in patients above 15 years of age was significantly low 22.37+0.05% for male, and 22.47£0.04% for female in comparison to 30.95%0.12% for male, and 31.15%0.15% for female in similar control group. The CD4"/CDS§" ratio mean in patients above 15 years of age was significantly low 1.63+0.004 for male, and 1.6£0.004 for female in comparison to 1.94+0.01 for male, and 1.890.01for female in similar control group. All patients with CL have zinc deficiency, and have decreased in CD4', CDS", and decreased CD4"/CD8" T lymphocytes.